Literature Review Study: The Role of Higher Education in Forming Human Resources with Character and Morals in Welcoming Golden Indonesia 2045 - Rohmatuz Zuhroh Sofwani; Tri Siwi Agustina; Mohd. Iqbal Azamuddin Zawizaz; Evania Yessica (Faculty of Education Universitas Negeri Malang, 2025)
Abstract : In connection with the important momentum for the Indonesian nation with the achievement of one hundred years of independence in 2045. Optimism from the prediction that at the age of one hundred, this nation will be inhabited by a productive age population. This study uses a literature review study method to explore the role of universities in forming human resources with character and morals in welcoming the golden Indonesia 2045. This study shows that character education plays an important role in producing superior and moral human resources, in accordance with the vision of the Golden Indonesia 2045. Universities play a strategic role not only in building academic competence, but also in forming student character through collaboration with the government, educators, and other stakeholders.